1998
DOI: 10.1149/1.1838360
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Stable Citrate Electrolyte for the Electrodeposition of Copper‐Nickel Alloys

Abstract: The stability of citrate electrolytes for the electrodeposition of copper-nickel alloys and multilayers has been investigated. It was found that electrolytes operating at pH 4 are unstable due to the formation of an insoluble citrate complex. This complex had previously been thought to be copper citrate dihydrate, Cu2C6H4O7'2H,O, but elemental analysis of the precipitate revealed it to be a heteronuclear copper-nickel citrate complex. Calculations of the distribution of citrate species in a typical plating sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 15 publications
2
59
0
Order By: Relevance
“…Previous data has shown that Ni ions adsorb to the surface of the Mt platelet [42]. Nickel is in excess in the solution because of the deposition conditions and most of the copper is complexed with citrate [44]. At pH values greater than 5, the heterobinuclear deprotonated species, CuNiCit 2 H 2 4− , predominate in the solution over the binary deprotonated species, Cu 2 Cit 2 H 2 4− .…”
Section: Atomic Absorption Spectroscopy and Energy Dispersionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous data has shown that Ni ions adsorb to the surface of the Mt platelet [42]. Nickel is in excess in the solution because of the deposition conditions and most of the copper is complexed with citrate [44]. At pH values greater than 5, the heterobinuclear deprotonated species, CuNiCit 2 H 2 4− , predominate in the solution over the binary deprotonated species, Cu 2 Cit 2 H 2 4− .…”
Section: Atomic Absorption Spectroscopy and Energy Dispersionmentioning
confidence: 98%
“…Figure 1 shows the TEM image of the Mt where the individual platelets can be seen after exfoliation. Citrate was used as the ligand in the electrochemical baths containing copper and nickel ions since citrate complexes with the metal ions [43][44][45]. The working, counter, and reference electrodes were a stainless steel substrate, coiled chromel wire, and a saturated calomel reference (SCE), respectively.…”
Section: Materials the Chemicals Used In The Plating Baths Werementioning
confidence: 99%
See 1 more Smart Citation
“…Bradley et al (1996) studied the nickel-copper alloy deposit from sulphamate electrolyte; Vu Quang et al (1985) and Abd El Rehim et al (1999) investigated the electrodeposition of nickel-copper alloy from citrate-based formulation and studied the effects of current, agitation, and temperature. Green et al (1998) also investigated the stability of citrate electrolyte and the effect of pH on alloy deposition. Dube et al (1995) made a detailed study on electroreduction of heterotetranuclear complexes during alloy deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The technological relevance of both citrate and citric acid in the field of electroplating processes is testified by their wide use as additives for the electrodeposition baths of several (mainly transition) metals and their alloys [3][4][5][6][7][8][9]. Electrochemical studies have, so far, focussed mainly on the reduction kinetics of the metal ions in the presence of citrate in the deposition bath [8].…”
Section: Introductionmentioning
confidence: 99%